Diagnostic Imaging for Thoracic Surgery A Manual for Surgeons and Radiologists (Springer International Publishing, 2018)
This book offers a comprehensive overview of thoracic pathologies of surgical interest involving the lung, mediastinum, esophagus, and chest wall with the aim of providing both radiologists and thoracic surgeons with a reference of high value in everyday clinical practice. Oncologic and non-oncologic conditions are reviewed from both the radiological and the surgical point of view, each one being documented with the aid of high-quality radiologic images from several modalities (including X-ray, fluoroscopy, CT, MR, and PET), illustrations/artwork, and high-definition images from the surgical table. The postoperative anatomy and complications associated with thoracic surgery procedures are also described in detail, with provision of imaging examples that highlight aspects of importance in differentiating between normal and abnormal findings. Written by experts in the field, Diagnostic Imaging for Thoracic Surgery is exceptional in combining precise descriptions of surgical procedures with key teaching points in imaging interpretation.